When credit turns political: Evidence from the Spanish Financial Crisis - Pia Hüttl; Simon Baumgartner (Deutsches Institut für Wirtschaftsforschung (DIW), 2023)
This paper provides causal evidence on the effect of credit crunches on political polarization. We combine data on bank-firm connections and electoral outcomes at the city-level during the 2008-2014 Spanish Financial Crisis. First, we show that firms in a relationship with weak banks experience a reduction in their loan supply and employment growth. Next, we estimate the effects of unemployment on voting behaviour. We construct an instrument for unemployment based on the city-level exposure to foreign weak banks. We find that a one standard deviation increase in instrumented unemployment translates into a 7 percentage increase in the polarisation of voters.
Keywords: G01; P16; D72; P43; 330; Polarization; Financial Crisis; Instrumental Variable Strategy; Spanish Elections; Credit Supply Shock; Real Effects; Unemployment Risk